2017
DOI: 10.1111/fwb.12884
|View full text |Cite
|
Sign up to set email alerts
|

Stream macroinvertebrate assemblage uniformity and drivers in a tropical bioregion

Abstract: Summary Understanding spatial and environmental drivers of undisturbed stream assemblages is important for separating natural and human‐induced changes, but has rarely been attempted for an entire tropical bioregion. We sampled riffle macroinvertebrate assemblages and measured associated biophysical variables in post‐wet and dry seasons from 68 streams of orders 1–5 across the Australian Wet Tropics, a small bioregion (18 497 km2) defined by its warm moist climate and closed‐forest vegetation. As climate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In PNG, flows have high day-to-day variability but low monthly variability (Yule and Pearson 1996) (Table 2). The AWT study sites were Birthday and Yuccabine Creeks in the uplands, and Pixies Creek in the lowlands, all having characteristics of other AWT low-order forest streams (Pearson et al 2017). The PNG sites were lowland low-order forest streams, Tam Creek and Creek 115, tributaries of the Ok Tedi River, which had similar characteristics to the AWT streams, apart from their contrasting hydrographs.…”
Section: Study Locationsmentioning
confidence: 99%
“…In PNG, flows have high day-to-day variability but low monthly variability (Yule and Pearson 1996) (Table 2). The AWT study sites were Birthday and Yuccabine Creeks in the uplands, and Pixies Creek in the lowlands, all having characteristics of other AWT low-order forest streams (Pearson et al 2017). The PNG sites were lowland low-order forest streams, Tam Creek and Creek 115, tributaries of the Ok Tedi River, which had similar characteristics to the AWT streams, apart from their contrasting hydrographs.…”
Section: Study Locationsmentioning
confidence: 99%
“…to these categories. Regarding benthic invertebrates, there is extensive evidence that organic matter content in sediments and granulometry are master variables affecting their distributions in large rivers (e.g., Blettler et al, 2016;Ezcurra de Drago et al, 2007;Pearson et al, 2017;Takeda & Fujita, 2004;Wantzen et al, 2014). For this reason, we consider that, at least for Oligochaeta, the upper catchment presents more heterogeneous habitats than higher order rivers.…”
Section: Discussionmentioning
confidence: 98%
“…The significant increase in Σω3 FAs and EPA proportions in shredders indicated that periphyton growth, and their FAs, increased on leaf litter and/or transported matter, as catchment urbanisation increased (Guo, Kainz, Valdez, Sheldon, & Bunn, ). An increase in proportions of Σω3 FAs and EPA of periphyton and macroinvertebrates may seem like beneficial responses to urbanisation, but these possibly could be outweighed by the negative and well‐documented effects of altered habitat, hydrology, and other stressors on the biomass and diversity of periphyton and macroinvertebrate communities (Hoyle, Kilroy, Hicks, & Brown, ; Moore & Palmer, ; Pearson et al., ; Roy, Rosemond, Paul, Leigh, & Wallace, ; Smucker & Detenbeck, ). Sensitive periphyton and macroinvertebrate taxa that thrive in minimally‐impacted systems are replaced by those with faster growth rates or higher P content under greater nutrient availability and by those more tolerant to altered habitat and deteriorated water quality (King et al., ; Morse, Wollheim, Benstead, & McDowell, ; Stevenson, Hill, Herlihy, Yuan, & Norton, ; Tsoi, Hadwen, & Fellows, ).…”
Section: Discussionmentioning
confidence: 99%